The Influence of Organizational Information Security Culture on Information Security Decision Making. (June 2015) - Parsons, Kathryn Marie; Young, Elise; Butavicius, Marcus Antanas; McCormac, Agata; Pattinson, Malcolm Robert; Jerram, Cate
In this study three aspects of information security decision making—namely, knowledge of policies and procedures, attitude towards policies and procedures, and self-reported behavior—were examined in conjunction with the organizational factors that may increase human-based cyber vulnerabilities. The results of a survey of 500 Australian employees revealed a significant, positive relationship between information security decision making and organizational information security culture. This suggests that improving the security culture of an organization will positively influence the behavior of employees, which in turn should also improve compliance with security policies. This means that risk to an organization's information systems and data will be mitigated. The complexity associated with implementing effective rewards and punishments are discussed, along with suggestions for further research to adequately understand the many factors that influence information security decision making.